2022
DOI: 10.1186/s12912-022-00923-0
|View full text |Cite
|
Sign up to set email alerts
|

Basic life support knowledge in a war-torn country: a survey of nurses in Yemen

Abstract: Background Successful implementation of Basic life support (BLS) is critical to improving survival rates and outcomes, especially among healthcare workers. To our knowledge, there is no available literature pertaining to the level of BLS knowledge of health care professionals in Yemen. Methods Data was collected for this cross-sectional descriptive study from June to August 2020, using a 10-item questionnaire related to cardiopulmonary resuscitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The pooled prevalence of Health Professional’s knowledge about basic life support in Ethiopia was 47.6 (95% CI: 29.90, 65.30). This finding is similar with study conducted at Pakistan(41.7%) [ 44 ], Yemen (53.6%) [ 45 ], Nigeria 43.6% [ 46 ] and Botswana 48% [ 47 ]. While this finding is lower than study conducted at India 64% [ 48 ], Islamic Republic of Iran 69% [ 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…The pooled prevalence of Health Professional’s knowledge about basic life support in Ethiopia was 47.6 (95% CI: 29.90, 65.30). This finding is similar with study conducted at Pakistan(41.7%) [ 44 ], Yemen (53.6%) [ 45 ], Nigeria 43.6% [ 46 ] and Botswana 48% [ 47 ]. While this finding is lower than study conducted at India 64% [ 48 ], Islamic Republic of Iran 69% [ 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…In a study conducted in Yemen in 2022 it was found that the knowledge of nurses there was below the acceptable levels to ensure maximum chances of survival in the event of cardiac arrest. Dissemination of BLS knowledge and providing training in the field in a more effective manner would offer the benefit of lives saved at minimal cost [16]. In a study from Nepal it was concluded that health workers' knowledge of basic resuscitation techniques was also inadequate [17].…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were established to omit senior administrative and managerial staff not directly involved in patient care, healthcare providers outside the scope of doctors and nurses, and individuals unwilling to participate in the study. The data collection process employed a validated instrument adapted from a preceding study (21), which was segmented into three distinct sections: demographic data, knowledge assessment, and an evaluation of attitudes and practices. The demographic section solicited information on participants' backgrounds.…”
Section: Methodsmentioning
confidence: 99%